Unisensory and multisensory temporal processing in autism and dyslexia: A systematic review and meta-analysis. (September 2020) - Meilleur, Alexa; Foster, Nicholas E.V.; Coll, Sarah-Maude; Brambati, Simona M.; Hyde, Krista L.
Highlights: Multisensory temporal processing is impaired in autism and dyslexia. In dyslexia, auditory and visual processing show a large impairment effect. Temporal processing is associated with literacy skills in dyslexia. In autism, temporal processing deficits extend to speech and nonspeech stimuli. Abstract: This study presents a comprehensive systematic review and meta-analysis of temporal processing in autism spectrum disorder (ASD) and developmental dyslexia (DD), two neurodevelopmental disorders in which temporal processing deficits have been highly researched. The results provide strong evidence for impairments in temporal processing in both ASD (g = 0.48) and DD (g = 0.82), as measured by judgments of temporal order and simultaneity. In individual analyses, multisensory temporal processing was impaired for both ASD and DD, and unisensory auditory, visual and tactile processing were all impaired in DD. In ASD, speech stimuli showed moderate impairment effect sizes, whereas nonspeech stimuli showed small effects. Greater reading and spelling skills in DD were associated with greater temporal precision. Temporal deficits did not show changes with age in either disorder. In addition to more clearly defining temporal impairments in ASD and DD, the results highlight common and distinct patterns of temporal processing between these disorders. Deficits are discussed in relation to existing theoretical models, and recommendations are made for future research.